Through a Green Gaze: Tentative Indicators of a Green 'Text' - Sally Harper; Wilhelm Johann Jordaan (Environmental Association of Southern Africa, 2009)
This paper seeks to re-claim for the idea 'green', something of the depth and range of its philosophical and ideological ideas at the time of its emergence and early formation from the 1960s to the 1990s, ideas which appear today to be largely unknown, forgotten or deliberately sidelined. It also seeks to provide for political, economic and environmental opinion-makers and decision-takers, a list of indicators by which to assess the green-ness of a 'text'. The paper is also useful for educators wishing to examine the philosophical foundations of their practice and the texts that they use in educational work.